2020
DOI: 10.7759/cureus.11860
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation and Frequency of Metabolic Syndrome in Women With Polycystic Ovary Syndrome: An Experience From a Tertiary Care Hospital in Pakistan

Abstract: Introduction: Polycystic ovary syndrome (PCOS) is a common endocrine disorder affecting women of reproductive age. The aim of this study was to determine the variations in the clinical presentation and frequency of metabolic syndrome (MetS) in women with PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…An Indian study represents similar findings, indicating that the metabolic dysfunctions are more distinct in obese females with PCOs than those without PCOs 21 . Furthermore, atherogenic dyslipidemia is also more common among obese females with PCOs than females without PCOs 22 . Obese females with PCOs showed a substantially high score on HOMA-IR as compared to the obese females without PCOs.…”
Section: Discussionmentioning
confidence: 99%
“…An Indian study represents similar findings, indicating that the metabolic dysfunctions are more distinct in obese females with PCOs than those without PCOs 21 . Furthermore, atherogenic dyslipidemia is also more common among obese females with PCOs than females without PCOs 22 . Obese females with PCOs showed a substantially high score on HOMA-IR as compared to the obese females without PCOs.…”
Section: Discussionmentioning
confidence: 99%
“…During the last decade, the prevalence of MS has increased in the general population -and this increase has been steeper in women, particularly in young ones. 2,5,9 A cross sectional study done at the Gynecologic Endocrinology Unit in Bangkok enrolled 250 PCOS Thai women who were diagnosed using Revised Rotterdam 2003 criteria and found the prevalence of MS by the definitions of NCEP ATP III to be 18.0%. 10 Several international studies showed variable frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…3 Overall, it is believed that both PCOS and metabolic syndromes are common in reproductive-aged women in the general population and that there is a substantial overlap between them. 4,5 In the present study, PCOS is defined based on the Rotterdam classification (ESHRE/ASRM), 2003 6 and MS is defined based on the International Diabetes Federation (IDF) definition Its clinical significance, although still debatable, lies in the fact that MS may predict a higher risk for cardiovascular events than the sum of the risks imparted by its individual components. According to one careful estimate, around 25% of world population has symptoms clearly indicative of MS. 7 Not surprisingly; untreated MS increases the risk of coronary and cerebro-vascular complications including death.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Polycystic appearances in ovaries were noted in 33.3 percent of the study populace in a study carried out at Baqai Institute of endocrinology, Karachi. 5 Diagnosis of PCOS is made according to the presence of at least two of the three criteria, i.e., polycystic ovaries on ultrasound, chronic anovulation, and increased androgens according to Rotterdam criteria. 6 Primary Subfertility is diagnosed when a couple has not achieved pregnancy after 2 years of having regular unprotected sex.…”
Section: Introductionmentioning
confidence: 99%